“MAX” Robot Pintar Berpendingin Mesin Dengan Sensor Suhu LM35 Berbasis Arduino UNO328P - Wahyuadnyana, Kadek Dwi; Wibawa, I Made Satriya (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2019)
It has been successfully created a robot named